Allergic predisposition modifies the effects of pet exposure on respiratory disease in boys and girls: the seven northeast cities of china (snecc) study - Dong Guang-Hui; Wang Jing; Liu Miao-Miao; Wang Da; Lee Yungling; Zhao Ya-Dong (BMC, 2012)
Abstract Background The relationship between pet exposure and the respiratory disease in childhood has been a controversial topic, much is still unknown about the nature of the associations between pet exposure and children's respiratory health stratified by gender and allergic predisposition. The objective of the present study was to assess the relationship between pet exposure and respiratory symptoms in Chinese children, and to investigate the modified effects of gender and allergic predisposition on such relationship. Methods 31,049 children were selected from 25 districts of 7 cities in Northeast China in 2009. Information on respiratory health and exposure to home environmental factors was obtained via a standard questionnaire designed by the American Thoracic Society. Results Children with an allergic predisposition were found to have more frequent exposure to pets than those without an allergic predisposition (18.5% vs. 15.4%). In children without an allergic predisposition, pet exposure was associated with increased susceptibility to respiratory symptoms/diseases, with girls being more susceptible than boys. No association was found between pet exposure and respiratory symptoms/diseases in boys with an allergic predisposition. In girls with an allergic predisposition, association was found between doctor-diagnosed asthma and pet exposure of their mother during pregnancy (adjusted odds ratio (ORs) = 2.03; 95% confidence interval (CI): 1.01-4.33), and their current pet exposure (ORs = 1.37; 95%CI: 1.00-1.88). Conclusions Pet exposure in children without an allergic predisposition was associated with increased susceptibility to respiratory disease, with girls being more susceptible than boys.